The Impact of COVID-19 on Participation, Effort, Physical Activity, and Well-Being of Sea Anglers in the UK - Hook, Samantha A.; Brown, Adam; Bell, Brigid; Kroese, Jo; Radford, Zachary; Hyder, Kieran (Frontiers in Marine Science, 2022)
Recreational sea angling is an important recreational activity in the United Kingdom with around 1.6% of adults participating and a total economic impact of around £1.5 billion each year. There are positive impacts of angling on physical health and mental well-being. The COVID-19 pandemic resulted in several national lockdowns in the UK, which along with additional local restrictions and personal circumstances due to the pandemic, have impacted people’s ability to fish. Angling was not allowed in the UK for some of the first lockdown (March to May 2020), and further restrictions were implemented subsequently that varied between the countries and regions. The impact of COVID-19 on the participation, effort, physical activity, and well-being of UK sea anglers remains unknown. A panel of UK sea anglers, which record their activity and catches as part of the Sea Angling Diary Project, were surveyed to assess changes in sea angling participation, physical activity, mental well-being, and expenditure between 2019 and 2020. We compared the sea angling effort and catches of the diary panel between 2019 and 2020. We found reduced sea angling effort in the panel, including sessions and catches, between 2019 and 2020, with the largest impact being in April 2020. We found that there was a significant reduction in expenditure during April 2020 with 64% of respondents spending less on sea angling than in a typical April. In total, 67% of respondents reported reduced happiness and 45% were less active due to sea angling restrictions. Using a general linear model, we found that even though anglers said that being able to go fishing has resulted in high World Health Organization Five Well-being Index scores, other factors also had significant effects. These included: age; physical and mental health status; angling activity; travel to fish during COVID-19; and whether they fished in July 2020. Of those who responded, 66% classified themselves as at either high or moderate risk to COVID-19. This work has shown that COVID-19 has negatively affected marine recreational fisheries in the UK, and not being able to go sea angling has negatively impacted participation, effort, physical activity and well-being.